Formation of thin film nanofibre of polyacrylic acid (PEO) - carboxymethylcellulose (CMC) – polyethylene oxide (PEO) by using electrospinning technique - Ahmad Idrus, Nurul Ashikin (2017)
Formation of thin film nanofibre of PAA-CMC-PEO was conducted via electrospinning technique. The purpose of this study is to study the electrospun film after blending the polymer of PAA-CMC-PEO. The purpose of this study is to determine the possibility of the polymer blended solution to be electrospun and secondly to characterize the electrospun nanofibre polymer blended of PAA-CMC-PEO. Three different solutions were prepared namely PAA-ethanol, PEO-water-ethanol and CMC-water before vigorously mixed together forming polymer blend solution at the ratio of 68:21:11. The blended solution of PAA-CMC-PEO was measured the viscosity and conductivity of the solution in order to determine the suitability of the solution to be electrospun. Morphology of the electrospun film was determined by using Field Emission Scanning Microscope (FESEM) and the diameter of the electrospun nanofibers was determined by using Image J software. The hydrophilic properties of the electrospun and pure conventional films were determined by using contact angle. Fourier Transform Infrared Spectroscopy (FTIR) was used to analyze the compound exist in the electrospun film after electrospinning. Based on the experimental result, it can be concluded that the electrospun nanofibre has successfully produced by using electrospinning technique with the ratio of blended solution of PAA-CMC-PEO, 68:21:11. The morphology of electrospun nanofibre was analyzed. The averafediameter of electrospun nanofibre is 400 ± 65 nm. The hydrophilic properties of the electrospun nanofibers was determined and it can be concluded the hydrophilic properties of PAA influence the hydrophilicity of the polymer blended electrospun nanofibers. The contact angle of electrospun nanofibre is 20.20⁰. All characteristic of polymers was exist in the electrospun nanofibre in the FTIR analysis with the finding of RC=O, OH, cellulose,C-O-C, CH₃ and C-O-H. It is proven that all three polymer exist in the polymer blended solution of PAA-CMC-PEO. Both objective achieved.